ANALYSIS OF EDUCATION POLICY AFTER THE COVID-19 PANDEMIC IN ELEMENTARY SCHOOL - Yulfia Nora; Ira Rahmayuni Jusar; Adek Nilasari Harahap; Rusdinal; Nurhizrah Gistituati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper identifies and analyzes education policies after the pandemic in elementary schools. Education policy refers to the legislation no. 20 of 2003, which aims to build a foundation of the whole nation in order to realize good educational standards. This legislation is in line with the legislation no. 23 of 2014, which states that local governments have authority in educational services because it is the government's obligation to fulfill basic community services. The method is carried out with descriptive qualitative. The method is used to describe imposed policies after the Covid-19 pandemic. The analyses are observations and interviews at three elementary schools in Padang. The research results indicate that education policies after COVID19 in elementary schools are retrieved from the regional head policies who are autonomous related to educational supervision during the outbreak that was carried out by monitoring elementary schools to show school preparation for face-to-face learning. Obstacles in implementing educational policies come from limited communication with students in terms of material explanation that demands to complete curriculum achievements.